Pembuatan Tepung Pisang (Musa Spp) dengan Mudah dan Praktis sebagai Bahan Baku Pangan Olahan - Reni Indrayanti; Rizal Koen Asharo; Pinta Omas Pasaribu; Rizky Priambodo; Vina Rizkawati; Yulia Irnidayanti (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Banana (Musa sp) is a priority fruit commodity which is able to be a supporting factor for the welfare of the community. Bananas are easily damaged fruits, so the selling value of bananas will decrease according to the age of the fruit after harvest. Storage of fruit in various temperatures also has not been able to extend the banana fruit shelf life. The potential of bananas as a food source that can be stored can be done through the processing of bananas into banana flour. The banana flour training carry out at the Biology Laboratory of FMIPA UNJ with a participant from RW 03 and 05 Rawamangun District. The making of banana flour is done in two technique. The first technique is to peel the skin previously then the fruit is immersed in a 10% salt solution for 10-20 minutes.  The second technique is done by steaming raw bananas for 10-20 minutes before stripping and soaking in a salt solution. Bananas that have been peeling are then slicing thinly to make cassava chips. Banana cassava is dried using sunlight for 2-3 days or dried in an oven at 150 °C for 2 days.  Dried cassava is mashed using a household scale flouring miller tool. Flour produced from the oven drying process is brownish-white, whereas by drying sunlight it is bone-white with a very fine texture. The results of the test carbohydrate content of banana flour produced had 56.72 g / 100 g starch content, 23.09 g / 100g amylose content and 33.63 g / 100 g amylopectin content.  The activity ended with giving banana flour samples produced in this activity and providing flour as an aid tool for community entrepreneurship.